Odpowiedzi

Najlepsza Odpowiedź!
2010-02-12T11:38:24+01:00

3-3x=3y+2
y+5=4x-3

-3x-3y=-3+2
y-4x=-5-3

-3x-3y=-1
-4x+y=-8 |*3

-3x-3y=-1
-12x+3y=-24
_______________
-15x=-25

-15x=-25 /(-15)
x=1⅔

y+5=4x-3
y+5=4*( 1 2/3)-3
y+5=20/3-3
y+5=3⅔
y=3⅔-5
y=-1⅓

x=1⅔
y=-1⅓


2010-02-12T11:40:55+01:00
3-3x=3y+2
y+5=4x-3

-3x=3y+2-3
y=4x-3-5

-3x=3y-1/:-3
y=4x-8

x=-y+1/3
y=4(-y+1/3)-8

x=-y+1/3
y=-4y+4/3-8

x=-y+1/3
y+4y=-20/3

x=-y+1/3
5y=-20/3

x=-y+1/3
y=-4/3

x=4/3+1/3
y=-4/3

x=5/3
y=-4/3

x=1. 2/3 (jedna cała i dwie trzecie)
y=-1. 1/3 (minus jedna cała i jedna trzecia)






2010-02-12T11:42:06+01:00
3-3x=3y+2
y+5=4x-3

-3x-3y=2-3
-4x+y=-3-5

-3x-3y=-1
-4x+y=-8→y=4x-8

-3x-3(4x-8)=-1
-3x-12x+24=-1
-15x=-1-24
-15x=-25
x=25:15
x=⁵/₃

y=4x-8=4×⁵/₃-8=-1⅓

spr.-3×⁵/₃-3×-⁴/₃=-1
-5+4=-1
-1=-1

rozw.:
x=⁵/₃=1⅔
y=-⁴/₃=-1⅓